2010
DOI: 10.1080/14759390903579232
|View full text |Cite
|
Sign up to set email alerts
|

The role of professional identity in patterns of use of multiple‐choice assessment tools

Abstract: This article uses the notion of professional identity within the framework of actor network theory to understand didactic practices within three faculties in an institution of Higher Education. The study is based on a series of interviews with lecturers in each faculty and diaries of their didactic practices. The article focuses on the use of a multiple-choice assessment tool available on a virtual learning environment and on the lecturers" attitudes towards it. The data suggests that the prevalent epistemic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…This would also be consistent with seeing ICT as multidimensional, ie capable of varied interpretation and application. The role of the educator in this context might become one of peering inside, and helping others to peer inside, the 'black box' of technology (Johannesen and Habibb, 2010). In contrast, a belief in social constructivist pedagogy implies greater certainty about particular teaching practices and a stable set of associations of technology with learner centred, and even, emancipatory pedagogy.…”
Section: Categorising Beliefs About Teaching and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…This would also be consistent with seeing ICT as multidimensional, ie capable of varied interpretation and application. The role of the educator in this context might become one of peering inside, and helping others to peer inside, the 'black box' of technology (Johannesen and Habibb, 2010). In contrast, a belief in social constructivist pedagogy implies greater certainty about particular teaching practices and a stable set of associations of technology with learner centred, and even, emancipatory pedagogy.…”
Section: Categorising Beliefs About Teaching and Learningmentioning
confidence: 99%
“…As with the literature on learning styles, the inventories used to categorise beliefs may be seen as lacking 'ecological validity' -teachers may be categorised out of the classroom as 'transmitters' or 'coexplorers' of knowledge but in the classroom they are pragmatists and adapt to the contexts in which they work. Beliefs, in some of the literature, appear to be 'constitutional' and fixed rather than constructed through social engagement and it is perhaps with this in mind Johannesen and Habibb (2010) prefer to discuss pedagogical belief in the context of negotiation of professional identity within a community of practice, rather than as internal constructs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Theories too tend to be used in a rather formulaic way in that they are transferred across to a technology context, rather than adapted to that context. Of course this is not always the case and, for example, Johannesen and Habib (2010) offer a flexible synthesis of two well-established sociological theories (in their case actor network theory and community of practice) in order to throw light on teachers' varied perceptions of multiple-choice software.…”
Section: Challenges In Theorisingmentioning
confidence: 99%
“…the teacher role, teachers' professional identity, and teachers' new skills and competences (see e.g. Comas-Quinn, 2011;Comas-Quinn et al, 2012;Crook and Cluley, 2009;Johannesen and Habib, 2010;Mattsson, 2008;Maddison, 2003, 2007;Morris et al, 2005). Examples of identified roles are cognitive, administrative and affective roles (ComasQuinn et al, 2012), as well as tutors, moderators and facilitators (ComasQuinn, 2011).…”
Section: Teaching With Learning Management Systemsmentioning
confidence: 99%
“…One example of these studies is Lawrence and Lentle-Keenan (2013) which studied the relation between teaching beliefs (thoughts on how teaching should be carried out), practice and institutional constraints when teaching with LMS in higher education. Another example is Johannesen and Habib (2010) which studied the relation between didactic practice and professional identity in the use of a specific feature of VLEs; multiple-choice assessment tools (MCAs). The study concluded that questioning the inscribed functionality in MCAs was related to the pedagogical beliefs held by the teachers, which in turn was related to the wider professional community in terms of faculties.…”
Section: Teaching With Learning Management Systemsmentioning
confidence: 99%